Investigation of Borax in Meatball Products Sold in Bengkalis, Riau - Zachawerus, Anjeli Cristina; Sulistiawati, Sulistiawati; Qurnianingsih, Ema (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Borax is still used as a food additive even though it has been banned.2. There was no relationship between age, income, and knowledge of the meatball sellers and the use of borax in Bengkalis.3. The risk factors for the widespread use of borax are still unknown. AbstractIntroduction: Borax is a food additive that can no longer be used. However, there were still many street food vendors who violated this rule. This study aimed to determine the presence or absence of borax in meatballs and the relationship between meatball sellers' characteristics and knowledge of the use of borax in Bengkalis, Riau.   Methods: This was an observational analytic study with cross-sectional collection. This study collected 40 samples of meatballs and meatball sellers in Bengkalis. The sampling technique used purposive sampling by interviewing meatball sellers and filling out the questionnaire on the spot. Data were analyzed by Chi-Square test.Results: This study found that all meatballs contained borax with 36 samples found to have borax content above the standard. This study also found no relationship between characteristics (age, level of knowledge, income) and knowledge of meatball sellers with the use of borax (p > 0.05).Conclusion: There was no significant relationship between borax use and meatball sellers' knowledge and characteristics.